Survei Motivasi Berolahraga Pada Peserta Didik - Purba, Oktary Zika; Iyakrus, Iyakrus; Bayu, Wahyu Indra; Victorian, Ahmad Richard (Jurnal Porkes, 2022)
The purpose of this study was to determine the exercise motivation of the students of SMP Negeri 3 Plakat Tinggi. This research method will use a survey method with a quantitative descriptive approach with survey techniques. The population is 112 students, and the research sample is 73 students. Collecting research data using a motivational exercise questionnaire with a validity and reliability level of 0.708 with a Likert scale. Analysis of research data using percentage descriptive analysis. The results of this study are a) Motivation to exercise motivation to exercise students of SMP Negeri 3 Plakat Tinggi based on intrinsic factors is 79.2 with a high category. b) Motivation to exercise motivation to exercise students of SMP Negeri 3 Plakat Tinggi based on extrinsic factors is 62.5 with a fairly high category. c) The motivation to exercise for the students of SMP Negeri 3 Plakat Tinggi is 70.5 with a fairly high category. The implication of this research is that by knowing the level of students' motivation to exercise, teachers must maintain and increase students' motivation in exercising.